A synthesis of person- and relational-level factors that influence bullying and bystanding behaviors: Toward an integrative framework. (July 2015) - Ettekal, Idean; Kochenderfer-Ladd, Becky; Ladd, Gary W.
Abstract: In this article, we attempt to integrate several theoretical models with the goal of explicating more broadly the determinants of bullying and bystanding behaviors. In particular, participant role perspectives (e.g., models in which bullying is conceptualized in the context of multiple participants) serve as an overarching frame for examining and formulating hypotheses about two additional types of determinants: (a) child attributes—specifically, the role of children's person-related development (i.e., social-cognitive, emotion, and moral processing), and (b) children's experience with multiple socializing agents (i.e., peers and teachers). Empirical evidence is reviewed to identify relevant constructs, and critical analyses of evidence within and across conceptual domains are utilized to formulate novel hypotheses about how person- and relational-level (socialization) processes may contribute to individual differences in bullying and bystanding behaviors.